Selective hydrogenation of cinnamaldehyde in supercritical CO2 over Pt/SiO2 and Pt/HS-CeO2: An insight about the role of carbonyl interaction with supercritical CO2 or with ceria support sites in cinamyl alcohol selectivity - Piqueras, Cristian Martin (2013)
The catalytic hydrogenation of cinnamaldehyde employing H2 as the reductant was carried out under supercritical (sc) CO2, propane and other CO2 dense mixture, employing Pt supported on silica and high surface (HS) ceria. The phase behavior of the mixtures was found to be in good agreement with the predictions obtained from the MHV2 (modified Huron-Vidal second-order) model. In order to study the influence of scCO2 on the selectivity, the reaction was also conducted in dense propane and near-critical CO2–isopropanol mixtures. These results were compared with those corresponding to classical gas–liquid conditions with isopropanol as solvent and low H2 pressure. In scCO2, the selectivity to cinnamyl alcohol over Pt/SiO2 was 91%, quite higher than under classical conditions (38%). Such an enhancement is originated by the interaction of the Cdouble bond; length as m-dashO with scCO2. For Pt/HS-CeO2 the selectivity under supercritical conditions was slightly lower (80%) than the one corresponding to Pt/SiO2 but quite higher than the one corresponding to gas–liquid conditions (54%). The interaction of the carbonyl group with ceria support predominates in this case, thus, the beneficial effect of scCO2 is not observed in the same magnitude as in the case of Pt/SiO2. A catalytic scenario is drawn for each catalyst in order to explain the different selectivity patterns.